2018
DOI: 10.1093/rpd/ncy210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Scan Range on Radiation Dose in the Computed Tomography Component of Oncology Positron Emission Tomography/Computed Tomography

Abstract: We performed phantom experiments to investigate radiation dose in the computed tomography component of oncology positron emission tomography/computed tomography in relation to the scan range. Computed tomography images of an anthropomorphic whole-body phantom were obtained from the head top to the feet, from the head top to the proximal thigh or from the skull base to the proximal thigh. Automatic exposure control using the posteroanterior and lateral scout images offered reasonable tube current modulation cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…An increase in effective dose would be somewhat less than that in the DLP. Extending the scan range to the feet increases the DLP; however, the distal thighs and legs lack radiosensitive organs or tissues, and therefore the effect of the extension on effective dose is negligible (Inoue et al 2019b). It should be noted that this study demonstrated the effects of imaging conditions on the DLP but not on effective dose or risk of stochastic effects.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…An increase in effective dose would be somewhat less than that in the DLP. Extending the scan range to the feet increases the DLP; however, the distal thighs and legs lack radiosensitive organs or tissues, and therefore the effect of the extension on effective dose is negligible (Inoue et al 2019b). It should be noted that this study demonstrated the effects of imaging conditions on the DLP but not on effective dose or risk of stochastic effects.…”
Section: Discussionmentioning
confidence: 66%
“…The arm position affects AEC-based dose modulation, and lowering the arms increases and decreases radiation exposure to the body and head, respectively (Inoue et al 2019a(Inoue et al , 2022. The PET/CT scan range may be from the skull base to the mid-thigh, from the vertex to the mid-thigh, or from the vertex to the feet (Boellaard et al 2015), and prolongation of the scan range increases DLP (Inoue et al 2019b). In PET/CT, respiratory motion may impair the quality and quantitative accuracy of PET images and spatial coregistration between PET and CT images, and thus PET is often performed with respiratory gating (Callahan et al 2011, Walker et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…According to these results, the use of the standard factor for head and torso (0.015 mSv/mGy⋅cm [36,37]) for CT studies including limbs may lead to large overestimation of final effective dose [33]. The k-factor for a CT covering from head to feet has been recently investigated by Inoue et al [38], who noticed a significant dependence on the AEC model. These authors obtained a conversion coefficient of 0.0100 mSv/mGy⋅cm when AEC is based on the AP scout, being in agreement with our estimation.…”
Section: Discussionmentioning
confidence: 97%
“…In positron emission tomography (PET)/CT, CT images from the head to the proximal thigh or foot are acquired in an imaging series, and the scanner provides a single DLP value. The DLP value may be multiplied by the conversion factor for the body trunk, which leads to an overestimation of the effective dose due to inaccurate estimation for the head, neck, and lower extremities [ 26 , 27 , 28 ]. In CT angiography and CT venography of the lower extremities, although irradiation to the lower extremities contributes significantly to DLP, the contribution to the effective dose is limited because of the low radiosensitivity of the lower extremities.…”
Section: Overview Of Ct Radiation Dose Managementmentioning
confidence: 99%
“…With our analysis procedures, problems in a small proportion of the scan range are difficult to find. For example, we found abnormally strong radiation exposure at the top of the head in the CT component of PET/CT through slice-by-slice evaluation of tube currents [ 27 , 32 ]. Such strong exposure occurred when using the posteroanterior localizer image alone for AEC but not when using the posteroanterior and lateral images.…”
Section: Daily Radiation Dose Managementmentioning
confidence: 99%